2018
DOI: 10.1108/inmr-05-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between favorable conditions for innovation in technology parks, the innovation produced, and companies’ performance

Abstract: Purpose Innovation is today considered a competitive differential for improving the performance of companies, and technology parks are seen as environments with favorable conditions for such innovation. The purpose of this study is to develop a framework for analyzing favorable conditions for innovation in technology parks, the innovations produced and organizational performance. Design/methodology/approach To this end, the authors conducted bibliographic research and in-depth interviews with managers of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
(183 reference statements)
0
6
0
Order By: Relevance
“…Thus, in this study, we were able to measure this complex causality and analyze it in terms of sufficiency and necessity based on a small sample using the fsQCA methodology. Previous research has supported the importance of parks in favoring the development of innovation by companies (Bonacina Roldan et al, 2018;Figlioli and Porto, 2012;Kharabsheh, 2012;Moudi and Hajihosseini, 2011). 2011) means presence of the condition.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, in this study, we were able to measure this complex causality and analyze it in terms of sufficiency and necessity based on a small sample using the fsQCA methodology. Previous research has supported the importance of parks in favoring the development of innovation by companies (Bonacina Roldan et al, 2018;Figlioli and Porto, 2012;Kharabsheh, 2012;Moudi and Hajihosseini, 2011). 2011) means presence of the condition.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
“…Specifically, the sample of companies used in this research belonged to a science and technology center and was characterized by high levels of innovation. The recipe that they followed, which can be used by companies who wish to innovate, is as follows: First, the relationship with other technology centers is the foremost component of the innovation recipe (Bonacina Roldan et al, 2018;Moudi and Hajihosseini, 2011;Vedovello et al, 2006). Openness to external sources allows firms to draw ideas from outsiders and deepen the pool of opportunities available to them (Albahari et al, 2017;Díez-Vial and Fern andez-Olmos, 2015;Díez-Vial and Montoro-S anchez, 2016;V asquez-Urriago et al, 2014).…”
Section: Implications For Management and Policymakersmentioning
confidence: 99%
“…On the contrary, users associate the TPs knowledge benefit only with information and training opportunities, suggesting that TPs should look beyond primary infrastructural support. The R&D facilities should also be their priority for mutual learning of tenant firms considering that it is vital for Pakistan because the digital entrepreneurial ecosystem is at a nascent stage, and collaboration for technological development and innovation is of utmost importance to compete at a global level (Roldan, Hansen, & Garcia-Perez-de-Lema, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of technologybased firms in high-technology sectors have observed substantial shortages of competent workers, which in turn undermines business growth and profitability (Sayer and Morgan 2018). Because most firms in Science Parks are technology-based and strongly dependent on access to qualified workers, researchers are beginning to focus on issues linked to the Science Parks that affect their ability to attract and develop customised talent solutions for their tenants (Bellavista and Sanz 2009;Bonacina Roldan et al 2018;Chen and Yu 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the popularity of Science Parks among researchers and the big interest in promoting entrepreneurship and regional development, very few papers have focussed on Science Park development the attraction of talent and the collaborations that occur regarding the talent attraction processes (Bellavista and Sanz 2009;Bonacina Roldan et al 2018). To our minds, the scarce knowledge in an area that has become of major import points to a clear knowledge gap.…”
Section: Introductionmentioning
confidence: 99%